From local monitoring to a global inventory of aquatic macrophyte introductions - insights for monitoring and preventing species invasions. - Dainez Filho, Mário Sérgio (2021)
Aquatic ecosystems are especially vulnerable to species invasion due to their extent, diversity of habitats, and inherent dynamics. Invasive aquatic macrophytes are of great concern because of their great influence on aquatic ecosystems. In this thesis, we sought to contribute to the field of biological invasions of aquatic macrophytes at regional and global levels using knowledge pertinent to monitoring and preventing the introduction of species. Given that, one of the most concerning invasive species in the world, Hydrilla verticillata (L.f.) Royle, was evaluated in different types of environments in a subtropical floodplain. The relationship of occurrences of this species with its main abiotic predictors was investigated, as well as its relationship with the native (equivalent) species Egeria najas Planch. right after its detection and 10 years later. This work contributed with insights regarding the biotic interactions of invaders and natives as well as changes in environmental predictors that highlight anthropogenic impacts that deserve attention. A second work was carried out to leverage knowledge about invasive aquatic macrophytes at a global level. A compilation of data from several available sources was carried regarding the most common pathways of introduction of aquatic macrophytes to identify the regions of origin and destination of these species and their respective functional groups. Such information is crucial for the determination of public policies and management strategies to avoid the introduction of unwanted species. In summary, this thesis helps the characterization of aquatic macrophyte invasions aiming at their prevention.